(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: In the treatment of Acute Coronary Syndrome (ACS), Prasugrel is recommended, alongside aspirin, for adult patients undergoing percutaneous coronary intervention (PCI) to prevent thrombotic events. Objective: This study aims to conduct a systematic review of the efficacy and safety of Prasugrel in ACS. Method: A systematic review method was used to search for studies meeting the inclusion criteria for analysis. Results: A total of 17 studies on safety and 10 studies on efficacy were included in the review. The compiled research findings also indicate that Prasugrel is relatively safe, with follow-up durations in studies typically ranging from 12 months, with the shortest being 30 days and the longest 10 years. Prasugrel has good safety, with life-threatening bleeding ranging from 0.1% to 2.2% and intracranial hemorrhage from 0.16% to 0.3%. There is no statistically significant difference in bleeding risk being found when compared Prasugrel with Ticagrelor. In terms of efficacy, Prasugrel helps reduce major adverse cardiovascular events (MACE) from 1% to 11.1%, and cardiovascular mortality from 0.6% to 3%. Conclusion: The evidence suggests that Prasugrel reduces the risks of cardiovascular events and shows its clinical benefits when compared with other P2Y12 receptor inhibitors.